The End of the Mina - Turner, J. P. (Oriens, 2010)
Abstract Why did al-Mutawakkil end the Mina? The usual answer to this question assumes that he was acknowledging the inevitable victory of the ulamā. He is seen to be ‘cutting his losses’ by restoring and enforcing orthodoxy as the traditionalist ulamā saw it. In this article I offer a different answer. Al-Mutawakkil ended the Mina as one part of his broader effort to establish his position as sovereign and independent of the individuals and structures that had carried over from al-Wāthiq’s reign. Eliminating the Mina was one strategy deployed in undermining and eliminating the “kingmakers” who had placed him on the throne. He correctly surmised that if left in place these would impede his position and ultimately control him.